Anxiety disorders in athletes - Reardon, C. L.; Gorczynski, P.; Hainline, B.; Hitchcock, M.; Rice, S. (Clinics in Sports Medicine, 2024)
Athletes experience many anxiety symptoms and disorders, including generalized anxiety disorder, panic disorder, and social anxiety disorder, at rates approximating those in the non-athlete population.